Insomnia, cardiorespiratory function and quality of life in individuals with post-COVID-19 fatigue - Nathalea Spode de Arruda; Alessandra Hofstadler Deiques Fleig; Charles Rech; Carine Cristina Callegaro (Sleep Medicine: X)
Objective: This study aimed to compare the prevalence of insomnia, lung function, inspiratory muscle function, functional capacity, and quality of life in individuals with and without post-COVID-19 fatigue. Methods: Thirty-four post-COVID-19 individuals participated in the study, 20 with fatigue (32 ± 12 years old, 15% male) and 14 without fatigue (31 ± 12 years old, 42.9% male). The Chalder Fatigue Scale (CFS) was employed to categorize the volunteers into two groups: those with fatigue (score ≥4) and those without fatigue (score <4). The Insomnia Severity Index (ISI) and the Epworth Sleepiness Scale (ESS) were used to assess insomnia and excessive daytime sleepiness, respectively. Pulmonary function was evaluated by spirometry, inspiratory muscle strength was assessed by the maximum inspiratory pressure (MIP), and inspiratory endurance was evaluated by maintaining an inspiratory load of 60% of MIP until fatigue. The 6-min walk test (6MWT) was used to evaluated functional capacity, while the WHOQOL-BREF questionnaire assessed quality of life. Results: Individuals with post-COVID-19 fatigue demonstrated a higher prevalence of insomnia (80% vs. 49%) and excessive daytime sleepiness (45% vs. 7%), as well as lower MIP, shorter distance covered in the 6MWT, and lower FEV1/FVC (forced expired volume in the first second divided by forced vital capacity), and FEV1/FVC% of predicted. Additionally, they exhibited poorer quality of life in the physical and environmental domains. CFS demonstrated a direct correlation with ISI (r=0.436, p=0.01) and ESS (r=0.593, p=0.001), as well as an inverse correlation with the distance covered in the 6MWT (r=-0.398, p=0.022) and FEV1 (r=-0.412, p=0.01). ISI was an independent predictor of CFS, with 62% of CFS variance explained by ISI variance. Conclusion: Individuals with symptoms of post-COVID-19 fatigue may have a higher prevalence of insomnia, reduced inspiratory muscle strength, functional capacity, and Tiffeneau index, along with impaired quality of life. ISI is an independent predictor of post-COVID-19 fatigue.